The Longitudinal Association Between Physical Activity and Physical Function in Older Women - Ward-Ritacco, Christie L.; Greaney, Mary L.; Clark, Phillip G.; Riebe, Deborah (Frontiers in Sports and Active Living, 2022)
Purpose: Though age-related decline in physical function is ameliorated by physical activity, less is known about changes in physical function in active versus inactive older women. The purpose of this study was to determine the longitudinal effects of physical activity on physical function in community-dwelling older women. Methods: 156 participants (age 78.3 ± 4.7) were dichotomized into two activity groups (inactive [IG]; n= 89 or active [AG]; n = 67) based on self-reported exercise at baseline. Repeated measures ANCOVA, controlling for age, measured differences in physical function between groups at baseline and 48-months using the timed up-and-go (TUG), 30-sec chair stand (30CST), and 30-second arm curl (30AC). Differences in TUG classification [normal (≤8.23 seconds); preclinical limitations/limited physical function (>8.23 seconds) by activity group were analyzed using chi square tests. Results: There was a significant main effect for activity group for the TUG (p=0.032) and 30AC (p=0.047). There were no significant group by time interactions, although TUG approached significance (p=0.052). A larger proportion of the IG than the AG (58.2 % vs. 86.5%, respectively) had TUG scores >8.23 seconds at 48-months (p <0.001). Within age groups, (< 80 years; ≥80 years), individuals in the AG were more likely to have normal TUG scores compared to those in the IG (χ2 (3, N=156) = 22.85, p <0.001). Conclusion: Older women who engaged in regular exercise at baseline had higher levels of objectively measured physical function at baseline and were less likely to have abnormal TUG scores at 48-months. These findings help illustrate the long-term benefit of exercise for older women.